The Fight Against the Plague in the Principality of Serbia, 1836–1838 - Milojević, Vesna O. (Collection of Papers of the Faculty of Philosophy in Priština, 2026)
The paper examines the health conditions during the plague epidemic that broke out in the Ottoman Empire in 1836 and, in the following year, reached the Principality of Serbia through the Aleksinac quarantine station, thereby threatening the borders of the Austrian Empire and the rest of Europe. From the quarantine, the disease first spread to Jagodina and the surrounding villages and subsequently reached the Valjevo District, including the villages of Brežđe and Osečina. During the epidemic, Prince Miloš demonstrated considerable skill in coordinating the entire civil administration to ensure the implementation of prescribed anti-plague measures. These measures were carried out responsibly and effectively in the affected areas with the assistance of local authorities. Through the establishment of a sanitary cordon, a network of quarantines, and the enforcement of strict sanitary regulations, the Principality of Serbia succeeded in containing the epidemic and preventing its further spread. In total, the plague claimed 230 lives.